2014
DOI: 10.1586/17476348.2014.948855
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of pulmonary nodules

Abstract: There are an increased number of pulmonary nodules discovered on CT scan images in part due to those performed for lung cancer screening. Risk stratification and patient involvement is critical in determining management ranging from interval imaging to invasive biopsy or surgery. A definitive diagnosis requires tissue biopsy. The choice of a particular biopsy technique depends on the risks/benefits of the procedure, the diagnostic yield and local expertise. This review will focus on the evaluation and manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 112 publications
2
22
0
Order By: Relevance
“…6,22,23 CT screening also decreased the patients' quality life because it can bring some levels of fear and anxiety regarding future transformation to cancer. 16,26 In accordance with this recommendation, our data also showed that patient age, nodule size and nodule margin were significantly different between tuberculoma and cancer. Approximately 67 million CT are currently performed annually in the United States and this number will be likely to increase significantly in the coming years.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…6,22,23 CT screening also decreased the patients' quality life because it can bring some levels of fear and anxiety regarding future transformation to cancer. 16,26 In accordance with this recommendation, our data also showed that patient age, nodule size and nodule margin were significantly different between tuberculoma and cancer. Approximately 67 million CT are currently performed annually in the United States and this number will be likely to increase significantly in the coming years.…”
Section: Discussionsupporting
confidence: 86%
“…18,20 Thus, understanding how to differentiate between tuberculoma and malignancy in these indeterminate solitary pulmonary nodule or mass has become more and more important. 16 Additionally, although the early detection of pulmonary cancer by low-dose CT reduces the mortality, low-dose CT screening significantly increases the number of indeterminate solitary pulmonary nodule in asymptomatic individuals, leading to a substantial amount of overdiagnosis. 16 Additionally, although the early detection of pulmonary cancer by low-dose CT reduces the mortality, low-dose CT screening significantly increases the number of indeterminate solitary pulmonary nodule in asymptomatic individuals, leading to a substantial amount of overdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the prevalence of low dose chest computed tomography screening, multiple primary lung cancers (MPLCs) are detected more frequently than in the past (31). However, the genetic profile, treatment, and prognosis of patients remain unclear.…”
Section: Nsclcmentioning
confidence: 99%
“…A handful of pathologies have been associated with a higher probability of developing cancer, and some examples of these are: Barrett’s esophagus, metabolic syndrome, Lynch syndrome and solid pulmonary nodules (58). When studying premalignant diseases that predispose cancer development, recent focus has been centered on the role of miRNA expression in increasing the risk.…”
Section: Clinical Trials Involving Mirnas and Cancermentioning
confidence: 99%